Process And Progress: Binding Precedents In The Civil Law And Common Law Traditions - Filho, Benedito Cerezzo Pereira (2016)
The present work investigates the consolidation of the stare decisis doctrine in common law, as the basis for understanding the phenomenon of deprecedentarization of trials recently introduced to the Brazilian legal framework, in order to evaluate its developmental potential. The main argument hereby presented wishes to demonstrate that the binding precedent microsystem, once established to create calculability and allow planning, may be theoretically essential for the development of a country and for the effectiveness of justice, through the foundation of the principles of legal security and equality, to allow the delivery of effective decisions.